Support for car-restrictive policies between individual affectedness, eco-consciousness, and fear of ecological gentrification - (:unkn) unknown (My University, 2026)
As cars account for about one sixth of all greenhouse gas emissions in Germany, a sustainable transformation of the German transport system is essential to combat climate change. However, effective policies to reduce private car use are often broadly unpopular. To better understand why, we conducted a representative survey of residents in two densely populated Berlin neighborhoods with extensive public transportation infrastructure in 2021 (N = 1041). With the help of the local municipality, we constructed three hypothetical scenarios (vignettes) of varying intrusiveness in restricting parking and other spatial privileges of private cars. We aim to identify the role of different individual-level factors for the acceptance of such policy measures: individual affectedness (habits of using private cars and other modes of transport), awareness of local problems caused by motorized private transport, general eco-consciousness, socio-economic status, and fear of rising rents in the neighborhood caused by the proposed policies. We find that individual affectedness, fear of rising rents, eco-consciousness, and, to a lesser extent local problem awareness explain about 56 % of the variation in residents' support for the policy. The socioeconomic status of residents (income, educational attainment, relative deprivation) is not an effective indicator of how they perceive car-restrictive policies. The fear of rising rents has not been widely acknowledged as a factor driving resistance to car-restrictive policies, and thus merits greater attention from both researchers and politicians.
Evidence from a vignette analysis in Berlin
Keywords: Autoverkehr; Individualverkehr; Einschränkung; Privatauto; Parkraumbewirtschaftung